KAJIAN PENERAPAN PERSAMAAN FUNGSI LOGARITMIS UNTUK MEMPREDIKSI KUAT TEKAN BETON DI BAWAH UMUR 28 HARI - Wibowo Wibowo; Endah Safitri; Teuku Rafi Baihaqi (Program Studi Teknik Sipil FT UNS, 2025)
The use of the maturity method to predict the actual compressive strength of concrete in construction projects is limited to same concrete mix designs that have undergone laboratory calibration tests. In the application of this method logarithmic equations are commonly used as model predictions because of their ease of use. Several studies has been done to compare logarithmic equation with other prediction model on concrete with binder subtitute. This experimental study aims to determine the suitability of using logarithmic equations in describing the compressive strength-maturity relationship in conventional concrete design mixes with different water-cement ratio (0.4; 0.45; 0.5; 0.55; 0.6) and with use of admixture in the form of 10% fly ash. The test object used is a concrete cylinder with a height of 30 cm and a diameter of 15 cm. Temperature measurements and concrete compressive strength tests were carried out at the ages of 1, 3, 7, 14, 21, and 28 days. The test data is depicted in the logarithmic equation curve and compared with the hyperbolic equation. The results showed that the logarithmic equation resulted in a higher coefficient of determination or lower error in 5 of the 6 mix designs used. Thus, the logarithmic equation has a good suitability for data testing and can be used to predict the compressive strength of concrete for the mix design used in this study.